Influence of Perfluorocarbon Liquids on Peripapillary Retinal Nerve Fiber–Layer Thickness Following Pars Plana Vitrectomy with Silicone Oil–Based Endotamponade - Maqsood, Sundas (Clin Ophthalmol, 2020)
BACKGROUND: Inner retina–layer modifications after pars plana vitrectomy (PPV) can be objectively assessed through spectral domain optical coherence tomography (SD-OCT). METHODS: This study explored prospectively changes in retinal nerve-fiber layer (RNFL) thickness with SD-OCT in eyes undergoing PPV with silicone oil–based tamponade with and without use of perfluorocarbon liquids (PFCLs) during the early postoperative phase (up to 3 months) at the Research Institute of Ophthalmology, Egypt. RESULTS: Thirty patients were recruited who underwent PPV and silicone oil–based tamponade for either retinal detachment or diabetic retinopathy between April 2019 and September 2019. Mean RNFL thickness showed no significant change during follow-up at the first week (102.90±30.68 mm), 1 month (107.30±32.27), or three months (105.90±36.68; p=0.46, 0.68). There were significant correlations noticed between RNFL thinning and axial length of eyes, intraocular pressure, and use of PFCLs during the follow-up period. CONCLUSION: The RNFL tends to change postvitrectomy, but not significantly. Careful examination and consistent follow-up is required for postvitrectomy patients with larger axial length and intraoperative PFCL use.